A Study of Factors Affecting Work Fulfilment among Academicians in Birgunj City of Nepal - Agrawal, Neha (Journal of Economics and Management, 2023)
Work fulfilment among the teachers has been found as a fundamental element influencing the performance of the organisation. The purpose of this study was to study the factors affecting work fulfilment among academicians in Birgunj city of Nepal. The variables included in the study are independent variables of Promotion & recognition, Peers, Salary & Incentives, Scholars and Physical setting with work fulfilment as a dependent variable. A descriptive and causal comparative research design using questionnaire method on 5-point Likert scale was used to collect and analyse the data. The study was conducted with the sample size of 150 academicians in Birgunj city of Nepal. The data were analysed through the use of descriptive statistics, correlation, multiple regression analysis and t-test using SPSS software. The findings of the study show that all the independent factors are important in determining the extent of work fulfilment among academicians working in Birgunj city of Nepal. Some factors like salary& incentives and physical settings are not found to have the significant influence on work fulfilment level of academicians.